Phylogeography of Kerivoula hardwickii in Sarawak using Cytochrome b gene - Fatin Najihah, Muhammad Lutfi (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The phylogenetics of Kerivoula hardwickii, an insect-eating bat which belong to family Vespertilionidae were inferred using 1,140 bp mitochondrial DNA Cytochrome b gene. It is observed to be widely distributed in the Southeast Asian region. Currently, studies have indicated that this species was understudied and lack of knowledge found especially on the genetic information. Altogether 30 individuals from Southeast and Northwest Sarawak were used in this study. The result showed no significant genetic variation among different K hardwickii populations in Sarawak. The findings also revealed that the K hardwickii populations were divided into two different primary clades, group 1 and group 2. Three haplotypes were found among the population and one was regarded as unique, while two others shared same haplotypes.